Jennifer Nash, and Samantha Pinto, editors. The Routledge Companion to Intersectionalities. Routledge Taylor & Francis Group, 2023. 673 pp. ISBN 978-0-367-65266-1 - Muhia, Arthur (FOCUS: Papers in English Literary and Cultural Studies, 2024)
The Routledge Companion to Intersectionalities is a recent scholarly multidisciplinary reference book devoted to both ancient and contemporary intersectional studies. It comprises nine parts which contain fifty-three chapters in total. The contributors’ team is made up of interdisciplinary scholars in the humanities and social sciences. The introductory section takes the concept of intersection, and explores the lived experiences, identities, and injuries of Black women, considering the multiple variables where axes converge. It uses this as a starting point to understand intersectionality as a key contemporary framework in feminist thought. Vital questions regarding intersectionality are asked and deliberated upon throughout the book. They include: “Is it a way to neutrally describe the multiplicity of identities that all subjects accrue? Is it an ‘oppression olympics,’ with the intersection as a site of accumulation of injury? Is it an analytic strictly ‘belonging’ to Black feminism—and to Black women—that includes an ethical and intel lectual imperative to focus on marginalized communities and identities? Is it a way of ‘doing’ feminism, both academically and in the world? Does it dismantle or build institutional affiliations across subjects, disciplines, and infrastructures?” (1).